Android 6 app development fundamentals - Deitel, Paul J. (LiveLessons., 2016)
"This online course is the professional programmer's guide to Java SE 7 and SE 8 development. With 8+ hours of instruction, Java Fundamentals Part I applies the Deitel signature live-code approach to teaching and explores the language and APIs in depth. Concepts are presented in the context of fully tested programs. The course features hundreds of complete programs with thousands of lines of proven Java™ code along with hundreds of tips that will help you build robust applications."--Resource description page.